Efektivitas Analgesik Ekstrak Temu Blenyeh (Curcuma Pupurascens Blume) pada Mencit Putih Jantan - Girly Risma Firsty; Indah Pramesti; Oktariani Pramiastuti (School of Pharmacy Institut Teknologi Bandung, 2024)
Pain is a sign of tissue damage in the body. Extracts from the Zingiberaceae family have been proven to be hypoalgesic agents and are superior to non-steroidal anti-inflammatory drugs. The aim of the research was to determine the analgesic effectiveness of the ethanol extract of temu blenyeh (Curcuma purpurascens Blume). The analgesic effectiveness test was carried out using the writhing method (Sigmund) on male white mice (Mus musculus) as test animals. The test animals used were 25 mice grouped into 5 consecutive treatment groups, namely Group 1 (aquadest), Group 2 (antalgin), group 3 (Dose 50 mg/kg BW), group 4 (Dose 100 mg/kg BW) and group 5 (Dose 150 mg/kg BW). The test sample was given orally, after 30 minutes the sample wasthen induced with 1% acetic acid intraperitoneally. Observed and calculated the cumulative number of writhing for 1 hour and calculated the percent writhing protection and percent analgesic effectiveness. The data obtained in the form of the cumulative number of stretches was analyzed by Anova test. The research results showed that the ethanol extract of temu blenyeh provided a percentage of protection respectively (44.5%; 50.14%; 57.64%) and the greatest percentage of analgesic effectiveness at a dose of 150 mg/kg BW of 99.07%. Data analysis showed that ethanol extract with a dose of 50; 100 and 150 mg/kg BW did not have a significant difference to the positive control, which means the sample had analgesic effectiveness.